Penerapan Sanksi Pidana Dan Sosial Bagi Pelaku Tindak Pidana Kekerasan Seksual - Yulius Efendi; Fathol Bari (Hakim, 2023)
Sexual violence can happen to anyone regardless of gender. The perpetrator of violence also allows the person closest to the victim. Sexual violence is increasing from year to year. In 2021 there were 1,902 and 2022 3.442 cases of sexual violence that occurred. Sexual violence can be physical and psychological. The state of Indonesia is experiencing serious violence and sexual harassment because the victims of sexual violence are mostly women, while the age of the victims of sexual violence is that most are children compared to adults. And the perpetrators are mostly adults. The government has made efforts to reduce this action by making existing regulations. As is the case in the Criminal Code regarding the concept of sexual violence contained in Articles 285 and 289. Article 285 regarding the maximum sentence for perpetrators of rape, namely 12 years in prison, while Article 289 regarding imprisonment for nine years for those who commit, threaten with violence, force or allow acts obscene The government has made efforts to reduce acts of sexual violence, by making statutory regulations that regulate sexual violence, the Law on Sexual Violence No. 12 of 2022 which was ratified on April 12, 2022, the legal basis for the protection of sexual violence against children in the Criminal Code, laws that regulate sexual violence in Indonesia. However, in reality it is still not effective, it is hoped that the government will make policies regarding actions taken for this sexual violence.